PENGARUH KOMPETENSI DAN INDEPENDENSI TERHADAP KUALITAS AUDIT - Rahmawati, Januar Dwi Widya (Jurnal Ilmiah Mahasiswa FEB, 2012)
Public accountant is independent auditor that provides services of audits on the financial statements and also service attestation other. The main task of public accountant is to check and give opinions regarding reasonableness financial report an entity based on standards set by the association ofÂ  indonesian accountants (IAI). Based on it, public accountant has responsibilities keeping the quality of audit that it produces. But on the other side the auditor also has another challenge that must be faced pressure from clients in various decision-making an auditor. If the auditor unable to resist the pressure from clients, itâ€™s mean pendency auditor has been reduced and could affect the quality of an audit. This research aimed to analyze and prove evidence empirical influence experience, knowledge, long associated with clients, and pressure from clients to the quality of the audit. Samples used 90 respondents that auditors found on 8 Office Public Acountant in Malang city according to directory IAPI 2012. While to answer hypothesis research, used a multiple regression analysis, that having previously done testing assumption classic. Based on the research, it can be concluded that knowledge, experience and long relationship with clients have a positive influence to the quality of the audit. So, as wide as the knowledge an auditor, as well as the more experienced of auditing, and as well as long time relationship with the client, it will be getting better the quality of the audit conducted. While pressure from clients have negative effects the quality of the audit, it was because disturb pendency auditors in decision making. Keywords : competence, pendency auditors, the quality of audit